Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Opioid Evaluation. (7th September 2021) - Wang, Marjorie C; Harrop, James S; Bisson, Erica F; Dhall, Sanjay; Dimar, John; Mohamed, Basma; Mummaneni, Praveen V; Hoh, Daniel J
Abstract: BACKGROUND: Opioid use disorders in the United States have rapidly increased, yet little is known about the relationship between preoperative opioid duration and dose and patient outcomes after spine surgery. Likewise, the utility of preoperative opioid weaning is poorly understood. OBJECTIVE: The purpose of this evidence-based clinical practice guideline is to determine if duration and dose of preoperative opioids or preoperative opioid weaning is associated with patient-reported outcomes or adverse events after elective spine surgery for degenerative conditions. METHODS: A systematic review of the literature was performed using the National Library of Medicine/PubMed database and Embase for studies relevant to opioid use among adult patients undergoing spine surgery. Clinical studies evaluating preoperative duration, dose, and opioid weaning and outcomes were selected for review. RESULTS: A total of 41 of 845 studies met the inclusion criteria and none were Level I evidence. The use of any opioids before surgery was associated with longer postoperative opioid use, and longer duration of opioid use was associated with worse outcomes, such as higher complications, longer length of stay, higher costs, and increased utilization of resources. There is insufficient evidence to support the efficacy of opioid weaning on postoperative opioid use, improving outcome, or reducing adverse events after spine surgery. CONCLUSION: This evidence-based clinical guideline provides Grade B recommendations that preoperative opioid use and longer duration of preoperative opioid use are associated with chronic postoperative opioid use and worse outcome after spine surgery. Insufficient evidence supports the efficacy of an opioid wean before spine surgery (Grade I). The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/1-preoperative-opioid-evaluation .